Exploring Matrix Multiplication with Manipulatives - Speakman, Maria; Courtney, Scott A. (Ohio Journal of School Mathematics, 2021)
The study of matrix operations and applications is required for students planning to take advanced courses, such as calculus, advanced statistics, or discrete mathematics. Furthermore, matrices appear on the ACT test and both SAT Mathematics Level 1 and Mathematics Level 2 subject tests. The student-centered activity presented here utilizes hands-on manipulatives, an attentiveness to student learning styles, group collaborative work, and whole-class reflective discourse. Finally, the activity engages students in several of the Standards for Mathematical Practice and helps students develop more robust meanings for matrix multiplication.